A Convenient Synthesis of 1,5-Fused 1,2,4-Triazoles from N-Arylamidines via Chloramine-T Mediated Intramolecular Oxidative N–N Bond Formation - Bhatt, Ashish; Singh, Rajesh K.; Kant, Ravi; Sarma, Bhupendra K. (Synthesis, 2019)
A convenient synthesis of 1,5-fused 1,2,4-triazoles from readily available N-arylamidines is reported. The reaction is efficiently promoted by chloramine-T to afford the desired products mostly in high yields and in relatively short time, through direct metal-free oxidative N−N bond formation. The mild nature of the synthesis and short reaction time are notable advantages of the developed protocol. This protocol is effective toward various substrates having different functionalities.
Keywords: N-arylamidine; [1,2,4]triazolo[1,5-a]pyridine; [1,2,4]triazolo[1,5-a]pyrazine; [1,2,4]triazolo[1,5-a]pyrimidine; chloramine-T; ethanol